The role of Artemisia turanica extract on renal oxidative and biochemical markers in STZ-induced diabetes in rat - Hassan Bagheri Yazdi; Mousa-; Vida Hojati; Abdolhossein Shiravi; Sara Hosseinian; Gholamhassan Vaezi (Mashhad University of Medical Sciences, 2020)
Objective: The aim of the current study was to investigate the protective effect of Artemisia turanica (AT) against diabetes- induced renal oxidative stress in rats. Materials and Methods: Fifty male Wistar rats were randomly divided into five groups: control, STZ-induced diabetic rats, diabetic rats+ metformin, diabetic rats + AT extract, diabetic rats+ metformin+ AT extract. In the present study, diabetes was induced by a single-dose (55 mg/kg, ip) injection of streptozotocin (STZ). Diabetic rats were daily treated with metformin (300 mg/kg), AT extract (70 mg/kg) and metformin+ AT extract for 4 consecutive weeks. Tissue activities of superoxide dismutase (SOD) and catalase and the levels of malondialdehyde (MDA) and total thiol content were measured in kidney tissue. Serum concentrations of glucose, creatinine, and urea, as well as, lipid profile were also measured. Results: STZ significantly increased the levels of glucose, triglyceride, urea and MDA compared to the control group. Total thiol content, as well as, catalase and SOD activities showed significant decreases in diabetic group when compared with the control animals. Serum glucose, triglyceride, cholesterol and renal MDA showed a significant decrease and renal total thiol and the activities of antioxidant enzymes showed significant increases in AT+STZ group compared with the diabetic group. In diabetic rats received AT+ metformin, serum LDL and HDL, renal MDA and SOD and catalase activities significantly improved compared with the diabetic rats. Conclusion: These findings suggested that AT extract has therapeutic effects on renal oxidative damage and lipid profile in diabetes, that possibly may be due to its antioxidant and hypolipidemic effects.